Foreign Investment Report of the Steering Group on Foreign Direct Investment - Planning Commission (Planning Commission, 2002)
The 2002 Planning Commission report on Foreign Direct Investment (FDI) in India examines global trends, identifies barriers to investment, and proposes comprehensive measures to enhance FDI inflows during the Tenth Plan period. Key challenges include regulatory complexity, procedural delays, poor infrastructure, and negative perceptions of India as an investment destination. Recommendations focus on regulatory and tax reforms, liberalizing sectoral investment caps, strengthening Special Economic Zones (SEZs), improving institutional frameworks like the FIPB and FIIA, and promoting India’s global image. The report also outlines procedures for the Infrastructure Authority to manage and monitor infrastructure projects, emphasizing private sector participation, risk management, and transparent project delivery mechanisms. Implementation of these reforms aims to create a favorable investment climate, attract international capital, and support India’s economic growth objectives.
Planning Commission Government of India New Delhi August 2022
Planning Commission Government of India New Delhi August 2022
Keywords: Foreign Direct Investment; FDI; Planning Commission India; Special Economic Zones; SEZ; Infrastructure Authority; Regulatory Reforms; Tax Incentives; Investment Climate; Disinvestment Policies; Sectoral Policy Reforms; Tenth Plan; Investor Engagement; Project Delivery; Private Sector Participation; Competitive Bidding; Risk Management; Infrastructure Financing; Legal Framework; Economic Growth